SALINE ARTHROGRAPHY OF THE DISTAL INTERPHALANGEAL JOINT FOR LOW‐FIELD MAGNETIC RESONANCE IMAGING OF THE EQUINE PODOTROCHLEAR BURSA: FEASIBILITY STUDY. Issue 4 (6th April 2015) - McGill, Shannon L.; Gutierrez‐Nibeyro, Santiago D.; Schaeffer, David J.; Hartman, Susan K.; O'Brien, Robert T.; Joslyn, Stephen K.
<x xml:space="preserve">Abstract</x> Abnormalities of the deep digital flexor tendon, navicular bone, and collateral sesamoidean ligament can be difficult to visualize using magnetic resonance imaging (MRI) if bursal fluid is absent. The use of saline podotrochlear bursography improves podotrochlear apparatus evaluation, however, the technique has disadvantages. The objective of this prospective feasibility study was to describe saline arthrography of the distal interphalangeal joint as an alternative technique for improving MRI visualization of the deep digital flexor tendon, navicular bone, collateral sesamoidean ligament, and podotrochlear bursa, and to compare this technique with saline podotrochlear bursography. Eight paired cadaver forelimbs were sampled. Saline podotrochlear bursography or saline arthrography techniques were randomly assigned to one limb, with the alternate technique performed on the contralateral limb. For precontrast and postcontrast studies using each technique, independent observers scored visualization of the dorsal aspect of the deep digital flexor tendon, palmar aspect of the navicular bone, collateral sesamoidean ligament, and podotrochlear bursa. Both contrast techniques improved visualization of structures over precontrast MR images and visualization scores for both techniques were similar. Findings from this study demonstrated that saline arthrography is feasible and comparable to saline podotrochlear bursography for producing podotrochlear bursa distension and separation of the structures of the podotrochlear apparatus on nonweight bearing limbs evaluated with low‐field MRI. Clinical evaluation of saline arthrography on live animals is needed to determine if this technique is safe and effective as an alternative to saline podotrochlear bursography in horses with suspected pathology of the podotrochlear apparatus.